Piper Reed, forever friend - Holt, Kimberly Willis (Henry Holt and Co., 2012)
Ten-year-old Piper moves yet again when her father, who is a Chief Petty Officer in the Navy, gets assigned to Norfolk, Virginia, and although the move takes a bit of adjustment, she soon makes friends with the girl next door and catches up with old friends too.